MINERAL CONTENT OF SURFICIAL SEDIMENT OF THE RANGSANG ISLAND AND ITS SURROUNDING AREA, MERANTI REGENCY, ARCHIPELAGO RIAU PROVINCE - Deny Setiady; Ediar Usman (BULLETIN OF THE MARINE GEOLOGY, 2015)
According to the regulation No 4 of 2009 of Mineral and Coal Mining Management stated that the requirement of an inventory for mineral resources data was created to support the establishment of mining area. This study is intended to obtain mineral resources content and surficial sediment data, Geographically the study area belongs to Meranti Archipelago Regency, Riau Province. it is located between 102o00'00" - 103o 15'00" E and 00o35'00" - 01o28'00" N. Grain size analyses result show that surficial sediment in the study area consists of silt, silty sand and sand which is dominated by silt. Based on the mineral identification, some of the minerals such as quartz, cassiterite, magnetite, hematite, dolonite, biotite and zircon have been found. Silt distribution is very wide started from estuarine southeast part northen part of Rangsang Island toward southeast of rangsang island. Sandy silt only found at the southeast of Rangsang Island, while sand sediment is found at the south and southeast of Rangsang Island. The presence of silt and sand grains is influenced by moderate to strong currents and wave patterns, so that the silt and sand grains sediment was transported along coastal to offsore area, while the fine grained (clay - silt) are deposited in the valley at the western part of Rangsang Island.Keywords: mineral, surficial sediment, Rangsang Island Berdasarkan Undang Undang Nomor 4 tahun 2009 tentang Pengelolaan Pertambangan Mineral dan Batubara, disebutkan bahwa inventarisasi data sumber daya mineral diperlukan dalam rangka mendukung penetapan Wilayah Pertambangan (WP). Penelitian ini dimaksudkan untuk memperoleh data kandungan sumber daya mineral dan sedimen dasar laut. Daerah penelitian, secara geografis termasuk dalam Kabupaten Kepulauan Meranti, Provinsi Riau, dan terletak pada koordinat antara 102o00'00" - 103o15'00" BT dan 00o35'00" - 01o28'00" LU. Hasil analisis besar butir menunjukkan sedimen permukaan dasar laut di daerah penelitian terdiri atas lanau, lanau pasiran dan pasir yang didominasi oleh lanau. Berdasarkan identifikasi mineral pada sedimen permukaan dasar lautnya menunjukkan kehadiran mineral kasiterit, magnetit, hematit, dolomit, biotit, zirkon dan kuarsa. Penyebaran lanau sangat luas dimulai dari daerah estuari barat laut dan bagian utara Pulau Rangsang, hingga ke sebelah tenggara Pulau Rangsang. Lanau pasiran hanya terdapat di tenggara Pulau rangsang, sedangkan pasir hanya terdapat di daerah di bagian selatan - tenggara Pulau Rangsang. Adanya butiran lanau - pasir dipengaruhi oleh pola arus dan gelombang yang sedang sampai kuat, sehingga butiran berukuran lanau - pasir dapat terangkut ke arah lepas pantai, sedangkan butiran halus (lempung) mengendap di daerah lembah di bagian barat Pulau Rangsang. Kata kunci: mineral, sedimen permukaan dasar laut, Pulau Rangsang